Pathways to trump: Republican voters in 2016. (October 2019) - Tucker, Patrick D.; Torres, Michelle; Sinclair, Betsy; Smith, Steven S.
Abstract: The 2016 candidacy of Donald Trump has drawn considerable interest among social scientists and it invites a broader investigation into analyzing the dynamics of primary elections. We identify four key popular accounts that supposedly explained Trump's support: authoritarianism, populism, ethnic prejudice, and trade and immigration attitudes, most of which are associated with an argument about support for Trump in the white working class. With a unique survey panel to explore changing support for Republican presidential candidates over the primary season, we test these competing theories and examine their fit to the pattern of support and opposition to Trump before and after the primaries. We find that populist attitudes and anti-Muslim bias were considerably more important than authoritarian dispositions, and immigration and trade policy attitudes in explaining support for Trump among Republicans during the 2016 primary season. We demonstrate how Trump's supporters became more diverse as they increased in numbers over the primary season, but new supporters were not a representative sample of Republicans who initially supported other candidates.